Pumpable plastic concrete using slag as aggregate and preparation method thereof
By using domestic waste incineration slag as concrete aggregate, combined with bentonite, clay and standard sand, the mix ratio design is optimized and pumped plastic concrete is prepared, which solves the problem of shortage of slag treatment and concrete materials, and has achieved resource utilization and performance improvement.
Patent Information
- Application Number
- CN202410822298.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-25
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-06-25
AI Technical Summary
Disposal of domestic waste incinerator slag and the shortage of sand and gravel for concrete.
Slag is used as concrete aggregate, combined with bentonite, clay and standard sand, and pumped plastic concrete that meets the engineering requirements is prepared by optimizing the mix ratio design and preparation method.
The resource utilization of waste slag has been realized, the shortage of sand and gravel for concrete has been alleviated, production costs have been reduced, and the mechanical properties and anti-seepage properties of concrete have been improved.
Smart Images

Figure CN118754548B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete, and in particular relates to a pumpable plastic concrete using slag as aggregate and a preparation method thereof. Background Art
[0002] Incineration of domestic waste is a relatively mature waste treatment technology that can achieve harmlessness, reduction and resource utilization of domestic waste. With the increasing pressure of waste disposal, the incineration of domestic waste has developed rapidly. However, the accumulation of waste incineration slag (referred to as "slag") produced by it has gradually become a problem that it cannot be disposed of. Domestic waste incineration slag contains sintered slag, glass, ceramics, bricks and a small amount of metal, accounting for about 80% of the waste incineration products. These slag particles have low heavy metal leaching toxicity, are loose and porous, contain certain cement aging products (C3S, C2S, C3A), have certain gelling activity, and generate gelling products after hydration reaction and volcanic ash reaction, which has resource utilization value. Therefore, domestic waste incineration slag can be used as porous aggregate in concrete engineering. Concrete is the most widely used building material in the world.
[0003] However, due to the country's high requirements for the protection of ecological resources, the supply of its raw materials, sand and gravel, has been drastically reduced, severely limiting the engineering application of materials such as concrete. Plastic concrete is a special type of concrete that has a lower cement content than ordinary concrete and is mixed with more bentonite, clay and other materials. The characteristics of this type of concrete include low strength, low elastic modulus and large strain, which makes it have good anti-seepage performance and is suitable for anti-seepage in water conservancy projects.
[0004] Taking the above into consideration, using domestic waste incineration slag as concrete aggregate can not only solve the increasingly serious problem of slag treatment and disposal, but also alleviate the shortage of sand and gravel for concrete. Summary of the invention
[0005] The object of the present invention is to provide a pumpable plastic concrete using slag as aggregate and a preparation method thereof in order to solve the above-mentioned problems.
[0006] The technical solution adopted by the present invention is as follows: a pumpable plastic concrete using slag as aggregate, characterized in that the concrete comprises:
[0007] cement;
[0008] Bentonite;
[0009] clay;
[0010] slag;
[0011] sand;
[0012] The water-cement ratio is 1.0, the cement content is 320, and the sand ratio is 69.2% to 74.2%.
[0013] In a preferred embodiment, the cement: uses P·O42.5 cement that meets the standard of GB175-2023 "General Portland Cement".
[0014] In a preferred embodiment, the bentonite is sodium-based bentonite having a basicity coefficient greater than or equal to 1.
[0015] In a preferred embodiment, the clay is selected from yellowish brown, loose to slightly dense soil mainly composed of silt and silty clay.
[0016] In a preferred embodiment, the slag is a continuous graded material with a particle size of 5 mm to 20 mm, and is derived from domestic waste incineration slag.
[0017] In a preferred embodiment, the sand is standard sand for concrete strength test produced by China Standard Sand Factory.
[0018] In a preferred embodiment, the preparation method comprises the following steps:
[0019] S1: First, carry out mix design and slag gradation analysis: determine the particle gradation of slag, define slag with a particle size of less than 5mm as fine-grained slag, which can approximately replace sand; define slag with a particle size between 5mm and 20mm as coarse-grained slag, which can approximately replace stone;
[0020] S2: Determine the initial sand ratio: According to the grading curve of the slag, the initial sand ratio is determined to be 64.2%;
[0021] S3: Adjust the sand ratio: adjust the sand ratio of aggregate to the target value by adding standard sand;
[0022] S4: Determine water consumption: adjust and determine the unit water consumption through indoor trial mixing;
[0023] S5: Calculate the amount of raw materials: Calculate the amount of cement, bentonite, clay, sand and slag according to the compressive strength and permeability coefficient requirements of plastic concrete and the determined water consumption;
[0024] S6: Orthogonal experimental design: using water-binder ratio, cement content and sand ratio as factors, 9 groups of mix ratios were designed for testing, and then the optimal mix ratio was obtained;
[0025] S7: Weigh cement, bentonite, clay, standard sand and slag respectively, and mix: pour cement, bentonite, clay and standard sand into a mixer and mix them evenly;
[0026] S8: Slowly add the calculated amount of water into the mixer, stir while adding water until the mixture is uniform, pour the mixed mixture into the mold, and vibrate to remove bubbles;
[0027] S9: Place the formed specimens in a curing room for curing. The curing cycle is 7 days and 28 days.
[0028] S10: Test the specimen after curing and record the data, after which the entire preparation process of the pumped plastic concrete using slag as aggregate can be completed.
[0029] In a preferred embodiment, in step S8, the mold should be clean, free of oil, and coated with a release agent.
[0030] In a preferred embodiment, in step S9, the curing temperature should be controlled within the range of 20°C ± 5°C to ensure normal development of concrete strength, and the curing humidity should be controlled above 95% to avoid water loss on the concrete surface and affect strength development. Curing time: The curing time should be no less than 7 days and can be appropriately extended according to the development of concrete strength.
[0031] In a preferred embodiment, in step S10, compressive strength and permeability coefficient tests are performed using a test instrument that complies with the standards.
[0032] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0033] 1. In the present invention, by using the slag from the incineration of domestic waste as concrete aggregate, the waste slag is utilized as a resource, the problem of slag treatment and disposal is effectively solved, and the shortage of sand and gravel for concrete is alleviated, the cost of concrete production is reduced, and significant economic and social benefits are achieved. In addition, by optimizing the mix design, the method can prepare concrete with compressive strength and permeability coefficient that meet the engineering requirements, so that it has good mechanical properties and anti-seepage performance, and meets the anti-seepage engineering needs in the fields of environmental geotechnical engineering and water conservancy engineering.
[0034] 2. In the present invention, bentonite, clay and other materials are added to improve the workability of concrete, so that it has good pumping performance, convenient construction and improved construction efficiency. In addition, the slag contains certain cement aging products and has certain gelling activity, which can improve the durability of concrete and extend the service life of the project. In summary, the preparation method has the beneficial effects of resource utilization of waste slag, good mechanical properties, working performance and durability, environmental protection benefits, economic benefits and social benefits, etc., and provides a new type of green building material for the construction industry with broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 It is the particle gradation curve diagram of the standard sand and slag of the present invention;
[0036] Figure 2 It is the effect curve diagram of compressive strength in the present invention. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0038] Reference Figure 1-2 ,
[0039] Example:
[0040] A pumpable plastic concrete using slag as aggregate, the concrete comprising:
[0041] cement;
[0042] Bentonite;
[0043] clay;
[0044] slag;
[0045] sand;
[0046] The water-cement ratio is 1.0, the cement content is 320, and the sand ratio is 69.2% to 74.2%.
[0047] Cement: Use P·O42.5 cement that meets the standard of GB175-2023 "General Portland Cement".
[0048] Bentonite: Use sodium-based bentonite with an alkalinity coefficient greater than or equal to 1.
[0049] Clay: Choose yellowish brown, loose to slightly dense soil mainly composed of silt and silty clay, containing plant roots, and the filling time is about 30 years.
[0050] Slag: Use continuous grade ingredients with a particle size of 5mm to 20mm, which comes from the slag from the incineration of domestic waste.
[0051] The sand used is standard sand for concrete strength test produced by China Standard Sand Factory.
[0052] The preparation method comprises the following steps:
[0053] S1: First, carry out mix design and slag gradation analysis: determine the particle gradation of slag, define slag with a particle size of less than 5mm as fine-grained slag, which can approximately replace sand; define slag with a particle size between 5mm and 20mm as coarse-grained slag, which can approximately replace stone;
[0054] S2: Determine the initial sand ratio: According to the grading curve of the slag, the initial sand ratio is determined to be 64.2%;
[0055] S3: Adjust the sand ratio: adjust the sand ratio of aggregate to the target value by adding standard sand;
[0056] S4: Determine water consumption: adjust and determine the unit water consumption through indoor trial mixing;
[0057] S5: Calculate the amount of raw materials: Calculate the amount of cement, bentonite, clay, sand and slag according to the compressive strength and permeability coefficient requirements of plastic concrete and the determined water consumption;
[0058] S6: Orthogonal experimental design: using water-binder ratio, cement content and sand ratio as factors, 9 groups of mix ratios were designed for testing, and then the optimal mix ratio was obtained;
[0059] S7: Weigh cement, bentonite, clay, standard sand and slag respectively, and mix: pour cement, bentonite, clay and standard sand into a mixer and mix them evenly;
[0060] S8: Slowly add the calculated amount of water into the mixer, stir while adding water until the mixture is uniform, pour the mixed mixture into the mold, and vibrate to remove bubbles;
[0061] S9: Place the formed specimens in a curing room for curing. The curing cycle is 7 days and 28 days.
[0062] S10: Test the specimen after curing and record the data, after which the entire preparation process of the pumped plastic concrete using slag as aggregate can be completed.
[0063] In step S8, the mold should be clean, free of oil, and coated with a release agent.
[0064] In step S9, the curing temperature should be controlled within the range of 20°C ± 5°C to ensure the normal development of concrete strength, and the curing humidity should be controlled above 95% to avoid water loss on the concrete surface and affect strength development. Curing time: The curing time should be no less than 7 days and can be appropriately extended according to the development of concrete strength.
[0065] In step S10, compressive strength and permeability coefficient tests are performed using a test instrument that meets the standards.
[0066] The present invention determines 9 groups of mix ratios through an orthogonal test of three factors and three levels (water-binder ratio 0.8, 0.9, 1.0; cement content 300, 320, 340; sand ratio 64.2%, 69.2%, 74.2%), and performs sample preparation and curing with the 9 mix ratios, with a curing period of 7 days and 28 days. The compressive strength and permeability coefficient of the samples are measured using a YES-S1000KN digital hydraulic pressure testing machine and a TSY-10 triaxial testing system, respectively, and the measurement results are subjected to range analysis and variance analysis, and a conclusion is drawn through the analysis results.
[0067] (1) The compressive strength and permeability coefficient of the samples prepared by the nine groups of mix ratios determined by the orthogonal test of three factors and three levels (water-binder ratio 0.8, 0.9, 1.0; cement content 300, 320, 340; sand content 64.2%, 69.2%, 74.2%) of the present invention all meet the requirements of the specification, and the maximum particle size of the aggregate does not exceed 20 mm, indicating that the scheme of using slag as concrete aggregate is feasible.
[0068] (2) Through extreme difference analysis, it was found that the optimal three-factor levels of slag pumped plastic concrete were 1.0 water-binder ratio, 320 cement content, and 69.2%-74.2% sand ratio, which greatly reduced the workload of on-site trial mixing, laid a foundation for subsequent research on the strength mechanism of slag pumped plastic concrete, and provided valuable experience for the actual on-site use of slag to prepare plastic concrete.
[0069] (3) Through variance analysis, it was found that the key indicators affecting the plastic concrete pumped by slag are water-cement ratio and cement content, indicating that when municipal solid waste incineration plants use slag as concrete aggregate, they only need to undergo simple treatment before they can be used as a good raw material, demonstrating the superiority of using slag in actual projects.
[0070] (4) The research results provide a reference for the effective utilization of industrial waste residues.
[0071] The experimental results are shown in Tables 1 to 9 below:
[0072] Table 1 Concrete mix ratio
[0073]
[0074] Table 2 Concrete test results
[0075]
[0076] Table 3 7d compressive strength range analysis table of orthogonal test
[0077]
[0078]
[0079] Table 4 Analysis of the range of 28d compressive strength of orthogonal test
[0080] factor Water-cement ratio Cement content Sand rate 28d compressive strength (MPa) 0.80 300 64.2% 4.56 0.90 320 64.2% 5.80 1.00 340 64.2% 5.27 0.80 320 69.2% 4.34 0.90 300 69.2% 5.16 1.00 340 69.2% 6.29 0.80 340 74.2% 3.64 0.90 320 74.2% 5.66 1.00 300 74.2% 5.46 <![CDATA[k 1 ]]> 4.180 5.060 5.210 <![CDATA[k 2 ]]> 5.540 5.267 5.263 <![CDATA[k 3 ]]> 5.673 5.067 4.920 R 1.493 0.207 0.343
[0081] Table 5 Analysis of the range of permeability coefficient at 28 days in orthogonal test
[0082] factor Water-cement ratio Cement content Sand rate 28d permeability coefficient (cm / s) 0.80 300 64.2% <![CDATA[4.53*10 -9 ]]> 0.90 320 64.2% <![CDATA[4.02*10 -9 ]]> 1.00 340 64.2% <![CDATA[1.32*10 -8 ]]> 0.80 320 69.2% <![CDATA[3.17*10 -8 ]]> 0.90 300 69.2% <![CDATA[8.56*10 -19 ]]> 1.00 340 69.2% <![CDATA[4.32*10 -8 ]]> 0.80 340 74.2% <![CDATA[2.20*10 -8 ]]> 0.90 320 74.2% <![CDATA[5.92*10 -9 ]]> 1.00 300 74.2% <![CDATA[5.16*10 -9 ]]> <![CDATA[k 1 ]]> <![CDATA[8.541*10 -8 ]]> <![CDATA[6.083*10 -9 ]]> <![CDATA[7.250*10 -9 ]]> <![CDATA[k 2 ]]> <![CDATA[6.167*10 -9 ]]> <![CDATA[1.388*10 -8 ]]> <![CDATA[2.782*10 -8 ]]> <![CDATA[k 3 ]]> <![CDATA[2.052*10 -8 ]]> <![CDATA[9.213*10 -8 ]]> <![CDATA[7.703*10 -8 ]]> R 7.924*10-8 <![CDATA[8.605*10 -8 ]]> <![CDATA[6.978*10 -8 ]]>
[0083] Table 6F Distribution Table
[0084]
[0085]
[0086] Table 7 Variance analysis table of 7d compressive strength results of orthogonal test
[0087] factor Sum of Squared Deviations Degrees of Freedom Mean Square F-number P-value Water-cement ratio 0.871 2 0.435 11.142 0.082 Cement content 0.181 2 0.091 12.321 0.301 Sand rate 0.179 2 0.090 2.297 0.303 error 0.078 2 0.039
[0088] Table 8 Variance analysis table of 28d compressive strength results of orthogonal test
[0089] factor Sum of Squared Deviations Degrees of Freedom Mean Square F-number P-value Water-cement ratio 4.263 2 2.131 5.176 0.162 Cement content 0.248 2 0.124 0.301 0.768 Sand rate 0.205 2 0.102 0.249 0.801 error 0.824 2 0.412
[0090] Table 9 Variance analysis table of 28d permeability coefficient results of orthogonal test
[0091] factor Sum of Squared Deviations Degrees of Freedom Mean Square F-number P-value Water-cement ratio <![CDATA[1.070*10 -14 ]]> 2 <![CDATA[5.348*10 -15 ]]> 1.473 0.40 Cement content <![CDATA[1.359*10 -14 ]]> 2 <![CDATA[6.794*10 -15 ]]> 1.872 0.35 Sand rate <![CDATA[7.713*10 -14 ]]> 2 <![CDATA[3.857*10 -15 ]]> 1.062 0.48 error <![CDATA[7.260*10 -14 ]]> 2 <![CDATA[3.630*10 -15 ]]>
[0092] Among the materials used in the present invention:
[0093] (1) Cement: P·O42.5 cement produced by Taicang Conch Cement Co., Ltd. was used. The physical and mechanical properties and chemical index test results of the cement all met the corresponding technical requirements of GB175-2023 "General Portland Cement".
[0094] (2) Bentonite: Sodium bentonite produced by Sichuan Renshou Xingda Industry and Trade Co., Ltd. is used, and its alkalinity coefficient is greater than or equal to 1.
[0095] (3) Clay: Soil was collected on site in Yancheng, Jiangsu Province. The soil is yellow-brown, loose to slightly dense, mainly composed of silt and silty clay, containing plant roots. It is generally revealed in the site area that it is mainly excavated earth from the existing Tongyu River and ship locks. The filling time is about 30 years. The survey revealed that the bottom depth of the fill layer is 0.50 to 4.50 m, and the survey revealed that the layer thickness is 0.50 to 4.50 m. It is mainly distributed on both sides of the upstream.
[0096] (4) Slag: The slag of the present invention comes from the incineration slag provided by the Longquanshan Municipal Waste Incineration Power Generation Project in Hefei City, Anhui Province, and is in the form of black-gray particles. According to the provisions of 4.1.7 of the "Technical Specification for Construction of Cast-in-Situ Plastic Concrete Anti-seepage Core Wall" JGJ / T291-2012, when the wall thickness is not more than 400 mm, the coarse aggregate should be selected from continuous grade ingredients with a particle size of 5 mm to 20 mm;
[0097] (5) Sand: The sand used in the test is standard sand for cement strength test produced by China Standard Sand Factory.
[0098] The mix ratio design of the present invention:
[0099] The present invention studies the effect of using slag as aggregate, so the definition of sand ratio is not the sand content divided by the total content of sand and stone as shown in formula (3-1), but an alternative definition as shown in formula (3-2). Before the test, the slag is graded and the gradation curve is drawn as shown in Figure 1 As shown, the particle size <5mm is defined as fine particle size slag, which is approximately considered to replace the fine aggregate of sand, and the slag of 5mm to 20mm is defined as coarse particle size slag, which is approximately considered to replace the coarse aggregate of stone. From the gradation curve of the slag, it can be considered that the initial sand ratio of the slag is 64.2%. The present invention controls the sand ratio of the aggregate by adding a certain amount of standard sand.
[0100]
[0101] Through indoor trial mixing, the unit water consumption is adjusted and determined, thus obtaining the amount of each raw material in the plastic concrete. According to the test results of the compressive strength and permeability coefficient of the plastic concrete, the mix ratio of the plastic concrete is proposed; with the water-binder ratio, cement content and sand ratio as the three factors of the experimental mix ratio design, 9 groups of mix ratios are designed, and the mix ratios are shown in Table 1.
[0102] Test method of the present invention
[0103] (1) Cube unconfined compressive strength test
[0104] A cubic specimen with a size of 150mm×150mm×150mm was made, and the compressive strength test was carried out on the 7d specimen and the 28d cubic specimen. When the curing time reaches the specified age, the cubic specimen is taken out from the curing room and covered with plastic wrap to prevent the specimen from losing water. After wiping the specimen clean, place it in the middle of the test machine platen, start the test machine, uniformly load at a rate of 0.05MPa / s to 0.1MPa / s and observe the specimen. When the specimen is close to failure and deforms rapidly, stop adjusting the throttle until the specimen fails. Record the load value at failure, and calculate the cube compressive strength value according to formula (3-1).
[0105]
[0106] Where:
[0107] P cc ——Unconfined cubic compressive strength of the material (MPa)
[0108] A——Compression area of the sample (cm 2 )
[0109] F——Failure load (kN)
[0110] (2) Cylindrical permeability test
[0111] A cylindrical specimen with a size of Φ100mm×100mm was made, and a permeability coefficient test was carried out on the 28d cylindrical specimen.
[0112] Results analysis of the present invention
[0113] In orthogonal tests, the range analysis method (intuitive analysis method) and variance analysis method are often used to analyze the test results. The range analysis of the test data can intuitively arrange the order of influencing factors; the variance analysis of the test data can be used to obtain the size of the test error, make up for the shortcomings of the range analysis, and thus improve the accuracy of the test. The orthogonal test was used to obtain the compressive strength and permeability coefficient data of slag concrete, and the range analysis and variance analysis methods were used to examine the influence of the three factors on the test indicators. The test results are shown in Table 2.
[0114] According to the "Technical Specification for Construction of Cast-in-place Plastic Concrete Anti-seepage Core Wall" JGJ / T291-2012, 4.3.2 Mechanical properties of plastic concrete stipulate that the 28d compressive strength should be 1.0MPa~5.0MPa and 4.3.3 stipulates that the permeability coefficient of plastic concrete should be 10-6cm / s~10-8cm / s. The measured data all meet the requirements of the specification.
[0115] According to 3.5.2 of "Technical Specification for Concrete Pumping Construction" JGJ / T10-2011, when the maximum particle size of coarse aggregate is 25mm, the minimum inner diameter of the delivery pipe is 125mm; when the maximum particle size of coarse aggregate is 40mm, the minimum inner diameter of the delivery pipe is 150mm. The maximum particle size of the sample aggregate prepared by the present invention is 20mm, which meets the requirements.
[0116] First, the range analysis was used for the compressive strength and permeability coefficient, and the calculation and analysis results are shown in Tables 3, 4 and 5. The magnitude and priority of the influence of each factor on the test index were discussed, and the magnitude of the test error and whether the influence of each factor on the test index was significant were given.
[0117] k1, k2, and k3 represent the average compressive strength (average permeability coefficient) of each factor at level 1, level 2, and level 3, respectively, and are used to reflect the influence of different levels of each factor on the compressive strength in order to obtain the optimal level of the factor. The range R of the compressive strength at different levels of a factor is used to reflect the degree of influence of the level change of the factor on the compressive strength. The larger the range, the more important the factor is, and vice versa, the factor is a secondary factor.
[0118] After analysis, the factors affecting the 7d compressive strength of slag plastic concrete in the orthogonal test are in the order of water-binder ratio>sand ratio>cement content. For the 7d compressive strength of slag plastic concrete, the larger the better. Therefore, the level of each factor that maximizes the K value is selected as the optimal level, that is, the factor level combination with higher compressive strength is water-binder ratio of 1.0, cement content of 320, and sand content of 74.2%. After analysis, the factors affecting the 28d compressive strength of slag plastic concrete in the orthogonal test are in the order of cement content>water-binder ratio>sand ratio. For the 28d compressive strength of slag plastic concrete, the larger the better. Therefore, the level of each factor that maximizes the K value is selected as the optimal level, that is, the factor level combination with higher compressive strength is water-binder ratio of 1.0, cement content of 320, and sand content of 69.2%. After analysis, the factors affecting the permeability coefficient of slag plastic concrete in the orthogonal test are in the order of cement content>water-binder ratio>sand ratio. For the permeability coefficient of slag plastic concrete, the smaller it is, the better. Therefore, the level of each factor that minimizes the K value is selected as the optimal level, that is, the factor level combination that obtains a lower permeability coefficient is a water-cement ratio of 0.8, a cement content of 300, and a sand ratio of 65.2%.
[0119] The effect curve diagram is a visual depiction of the orthogonal test intuitive analysis table, which represents the mean effect curve diagram of each level result of each factor in the table, such as Figure 2 shown.
[0120] From Figure (a), it can be concluded that the compressive strength of slag plastic concrete increases with the increase of water-binder ratio, and with the increase of water-binder ratio, the increase of compressive strength tends to slow down. From Figure (b), it can be concluded that the compressive strength of slag plastic concrete increases first and then decreases with the increase of cement content, indicating that the cement content should be controlled when designing the mix ratio of plastic concrete. Too much cement content will affect the increase of bonding strength. From Figure (c), it can be concluded that the compressive strength of slag plastic concrete is affected by the interaction of sand ratio and time, resulting in its strength change trend not showing similar characteristics.
[0121] The SPSS software was used to perform variance analysis on the orthogonal test results of slag plastic concrete mix ratio, test the significance of the influence of each factor and analyze the influence of test error. Let the value of a be 0.1, 0.05, and 0.01, that is, the confidence level is 90%, 95%, and 99%, respectively. The F distribution table is shown in Table 6, and the calculation results are shown in Table 7, Table 8, and Table 9. If the F value is greater than the F critical value, it means that the significance level of the factor on the test results is a, that is, there is a 1-a confidence to determine that the conclusion is correct. At the same time, a difference analysis is performed based on the P value. P>0.05 indicates that the factor does not show significance for the concrete index.
[0122] From the above table, we can see that the variance analysis (full name is single factor variance analysis) is used to study the differences of the three indicators of 7d compressive strength, 28d compressive strength and 28d permeability coefficient for the three factors of water-binder ratio, cement admixture and sand ratio. It can be seen from the above table that:
[0123] (1) Different 7d compressive strength, 28d compressive strength and 28d permeability coefficient (three indicators) do not show significance (p>0.05) for water-cement ratio, cement admixture and sand ratio (three factors), which means that the three indicators show consistency for all three factors and have no differences. The reason for the analysis is that the degree of freedom is set to 2, which is relatively small, only 2, which masks the significance of the factors.
[0124] (2) For the 7d compressive strength of slag plastic concrete, the F ratio of the water-binder ratio and cement output is greater than the F critical value at a confidence level of 90%, that is, it reaches the significance level, while the sand ratio does not reach the significance level. The reason for this is that the standard sand added cannot fill the gaps between slag particles well, and the strength improvement effect is not obvious.
[0125] The sum of squares of the deviations of the three factors in the 7d compressive strength results are all greater than the sum of squares of the deviations of the errors, indicating that the results of the orthogonal test of slag plastic concrete are reasonable; the sum of squares of the deviations of cement content and sand ratio in the 28d compressive strength results are less than the sum of squares of the deviations of the errors. Analysis shows that this is due to interference from environmental factors during the curing process.
[0126] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the term "comprise" or any other variant thereof is intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the presence of other identical elements in the process, method, article or device including the elements.
[0127] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A pumpable plastic concrete using slag as aggregate, characterized in that: The concrete comprises: cement; Bentonite; clay; slag; sand; The cement: P·O42.5 cement conforming to the standard of GB175-2023 "General Portland Cement" is used; The bentonite is sodium-based bentonite with a basicity coefficient greater than or equal to 1; The clay is selected from yellow-brown soil mainly composed of silt and silty clay; The slag is derived from the slag from the incineration of domestic waste; The sand is standard sand for concrete strength test produced by China Standard Sand Factory; The preparation method of pumped plastic concrete comprises the following steps: S1: First, carry out mix design and slag gradation analysis: determine the particle gradation of slag, define slag with a particle size of less than 5mm as fine-grained slag, which can approximately replace sand; define slag with a particle size between 5mm and 20mm as coarse-grained slag, which can approximately replace stone; S2: Determine the initial sand ratio: According to the grading curve of the slag, the initial sand ratio is determined to be 64.2%; S3: Adjust the sand ratio: adjust the sand ratio of aggregate to the target value by adding standard sand; S4: Determine water consumption: adjust and determine the unit water consumption through indoor trial mixing; S5: Calculate the amount of raw materials: Calculate the amount of cement, bentonite, clay, sand and slag according to the compressive strength and permeability coefficient requirements of plastic concrete and the determined water consumption; S6: Orthogonal experimental design: With water-binder ratio, cement content and sand ratio as factors, 9 groups of mix ratios were designed for testing, and then the best mix ratio was obtained, in which the water-binder ratio was 1.0, the cement content was 320, and the sand ratio was 69.2% to 74.2%; S7: Weigh cement, bentonite, clay, standard sand and slag according to the best mix ratio, and mix: pour cement, bentonite, clay and standard sand into a mixer and mix them evenly; S8: Slowly add the calculated amount of water into the mixer, stir while adding water until the mixture is uniform, pour the mixed mixture into the mold, and vibrate to remove bubbles; S9: Place the formed specimens in a curing room for curing. The curing cycle is 7 days and 28 days. S10: Test the specimen after curing and record the data, after which the entire preparation process of the pumped plastic concrete using slag as aggregate can be completed.
2. The pumpable plastic concrete with slag as aggregate according to claim 1, characterized in that: In step S8, the mold should be clean, free of oil stains, and coated with a release agent.
3. The pumpable plastic concrete with slag as aggregate according to claim 1, characterized in that: In step S9, the curing temperature is controlled within the range of 20°C ± 5°C; the curing humidity should be controlled above 95%; and the curing time is no less than 7 days.
4. The pumpable plastic concrete with slag as aggregate according to claim 1, characterized in that: In the step S10, compressive strength and permeability coefficient tests are performed using a test instrument that complies with the standards.